Using mind mapping and five reviewing patterns to improve senior high school students’ vocabulary mastery - Dian Fadhilawati (Jurnal Linguistik Terapan, 2012)
This reported research was a collaborative action research to improve the vocabulary achievement of high school students using mind mapping and five reviewing patterns proposed by Buzan (2009). The subjects were 35 students of X-B class of MAN Kota Blitar, East Java, Indonesia, in 2011/2012 academic years. The data of the research included qualitative data (observation result and field note) and quantitative data (test result). This research was conducted in one cycle which included 2 meetings. The first meeting was done at Tuesday, 7 February 2012. It was for teaching vocabulary about newspaper and publishing using mind mapping and review 1. The second meeting was done at Wednesday, 8 February 2012. It was for teaching vocabulary about radio and television as well as for the review 2 at the beginning of the meeting. At the end of the meeting, the teacher gave take home tasks for review 2 of meeting 2. Further, the third review (1 week after the first learning) was given at Wednesday, 15 February 2012. It was intended for reviewing both the materials in meeting 1 and 2. The fourth review was a take home reviewing tasks given 1 month after the first learning and the fifth review was a take home review assigned 3 months after the first learning. After all of the five reviews, a vocabulary test was administered. The finding showed that the implementation of mind mapping and 5 reviewing patterns could improve the students’ vocabulary achievement, from the mean score of 55.66 to 80.57. The students also gave positive responses toward the strategies applied as reflected from the result of the questionnaire given.